A randomized, double-blind trial evaluating the efficacy and safety of monotherapy with the once-weekly dipeptidyl peptidase-4 inhibitor omarigliptin in people with type 2 diabetes. (April 2018) - Home, Philip; Shankar, R. Ravi; Gantz, Ira; Iredale, Carol; O'Neill, Edward A.; Jain, Lokesh; Pong, Annpey; Suryawanshi, Shailaja; Engel, Samuel S.; Kaufman, Keith D.; Lai, Eseng
Highlights: Omarigliptin is a once-weekly oral DPP-4 inhibitor. Omarigliptin was evaluated as monotherapy in people with T2DM. After 24 weeks omarigliptin was superior to placebo in reducing HbA1c. Over 54 weeks omarigliptin was generally safe and well tolerated. No symptomatic hypoglycemia or weight gain was observed with omarigliptin. Abstract: Aims: To assess the efficacy and safety of once-weekly omarigliptin as monotherapy in people with type 2 diabetes mellitus (T2DM). Methods: People with T2DM not on glucose-lowering medications, or who were washed off monotherapy or low-dose dual therapy, were randomized double-blind to omarigliptin 25 mg (n = 165) or matching omarigliptin placebo (n = 164) for 24 weeks, followed by a 30-week period to assess continuing efficacy and safety longer-term of omarigliptin during which metformin was added to the placebo group and metformin placebo to the omarigliptin group. Results: From a mean baseline HbA1c of 8.0–8.1%, the least squares mean (95% CI) change from baseline in HbA1c at week 24 (primary endpoint) was −0.49% (−0.73, −0.24) in the omarigliptin group and −0.10% (−0.34, 0.14) in the placebo group, for a between-group difference of −0.39% (−0.59, −0.19) (p < .001). Protocol deviation in use of metformin by 38 of 252 (15%) people whose samples were available for evaluation probably attenuated glycemic efficacy results, as suggested by the LS mean difference −0.53% (−0.75, −0.32) after censoring of such participants. At 24 and 54 weeks, the incidences of adverse events (AEs) were similar in the omarigliptin and placebo groups. During 54 weeks there were no AEs of symptomatic hypoglycemia in the omarigliptin group and 5 AEs in the placebo group. Over 54 weeks, a majority of the omarigliptin treatment had a persistent reduction in HbA1c, remaining rescue-free. Conclusions: In people with T2DM, omarigliptin monotherapy improved glycemic control over 54 weeks and was generally well tolerated with a low risk of hypoglycemia. ClinicalTrials.gov Identifier: NCT01717313. EudraCT Number: 2012-003626-24.